Zeroing dynamics method for motion control of industrial upper-limb exoskeleton system with minimal potential energy modulation. (15th October 2020) - Li, Zhan; Zuo, Wenkun; Li, Shuai
Highlights: Minimal modulation of potential energy of the upper-limb exoskeleton. An optimization criterion constrained with the potential energy. Zeroing dynamics is applied to solve the optimization promisingly. Simulation and experiment results validate the proposed method. Abstract: Accurate motion control of industrial upper-limb exoskeleton can provide efficient assistance for subjects to perform various industrial manipulation tasks. In most motion control scenarios of upper-limb exoskeletons, the variations of potential energy frequently reach to a high level of oscillations, leading to the reconstructed motion uncomfortable or dangerous. In this paper, in order to achieve minimal potential energy variation and accurate motion control of the upper-limb exoskeleton, we propose a novel motion planning strategy with minimal potential energy modulation. Such motion resolution scheme is formulated as an optimization problem and solved by the zeroing dynamics (ZD) to achieve elegant global convergence. Simulation and experiment results show that the potential energy variation range of the upper-limb exoskeleton can be significantly decreased by average 99.34 % in both X - Y and X - Z planes, in addition to finishing tracking the desired motion path accurately. All of these demonstrate that the efficiency and superiority of the proposed method for potential energy minimization during achieving accurate motion planning and control.